Beyond the Factory Walls: Assessing Community Health Impacts of Industrial Operations through Industrial Hygiene Tools - Holt, Kimberly Long (Indonesian Journal of Advanced Research, 2025)
The abstract in the study attracts attention to the health risks of industrial operations, particularly in the low-income neighborhood within the area, owing to the radiation, noise, and emissions. The objective of the research will be to establish the use of industrial hygienic gadgets, including air quality screeners, noise dose, and radiation surveillance, to quantify and protect this impact on the common good. The paper gives the medical complications of industrial exposure, such as respiratory and cardiovascular conditions, and the challenge of beginning to assess the health statuses in society. The paper concludes by asking the question that more powerful policies should be designed to establish stronger environmental policies, promote localized surveillance systems, and develop a concept that can be used to defend the health of the vulnerable population through adherence to the industrial hygiene instruments in the context of environmental justice.